A Conceptual Enquiry on the Role of Academic Incubators in Nurturing Entrepreneurship among Students - Sultana, Nazia; Yugendhar, Akkinapally (International Journal of Engineering and Management Research, 2025)
Educated youth of India are finding it difficult to secure jobs and have an economically viable livelihood. To help the economy grow and create new jobs, the government needs to encourage new ideas and put money into the education of the next generation of workers. Entrepreneurship development can be a big part of the fight against unemployment and the growth of the economy as it makes possible conversion of innovative ideas into new businesses or start-ups resulting in creation of jobs. The government and the higher education institutes (HEIs) should work together to create an environment that is conducive to the launch of new businesses and shift the mindset of educated young people towards the pursuit of self-employment rather than job hunting. Many state governments, in conjunction with the central government, have enacted legislation to provide assistance to newly founded firms in their respective areas. And higher education institutions have also established incubation centers to nurture and assist entrepreneurial fervor among students. In a start-up ecosystem, in addition to the government, there are a wide variety of other institutions and ecosystem facilitators that provide assistance to start-up units. Some examples of these ecosystem facilitators and institutions include incubators, accelerators, educational institutions, research institutions, investors, and mentors (NGOs). Higher education institutions and universities are playing a significant role in the promotion of new business ventures and the provision of platforms for enterprise creation. The study hypotheses, given the current entrepreneurial ecosystem in India, that entrepreneurship among students can be directly linked to the support offered to them by the academic incubators. The current study proposes a model for the establishment and operation of startup incubators within academic institutions, so that entrepreneurial fervour can be nurtured among students.